"I'm not in this alone" the perspective of parents mediating a physical activity intervention for their children with autism spectrum disorder. (December 2018) - Healy, Seán; Marchand, Geneviève; Williams, Edward
Abstract: Background and aims: Web-based, parent-mediated interventions have shown to be beneficial for children with autism spectrum disorder (ASD) in a variety of domains. We aimed to examine how parents of children with ASD perceive mediating a physical activity intervention delivered via a private Facebook group. Methods: Thirteen families participated in a four-week trial of Project CHASE. Inductive thematic analysis of semi-structured interviews and interactions within the Facebook group were conducted to elicit the perspective of the parents. Outcomes and results: Thematic analysis resulted in three themes emerging: (1) 'Remembering to Act' encompassed the participants' perspectives of Project CHASE as being an intervention that reminded them of the importance of physical activity, and served as a prompt for them to take action; (2) 'A sharing community' included the subthemes of 'sharing success and struggles' and 'sharing ideas'; and, (3) 'Taking control: possibilities and problems' encapsulates the dichotomy between participants who spoke of embracing and rising to the challenge of taking control, with the parents who spoke of the need for more support, direction, and guidance. Conclusion and implication: The current study suggests parent-mediated, web-based interventions may have the potential for improving the effectiveness of physical activity interventions for children with ASD.